Youth justice and racialization: Comparative reflections. (August 2020) - Cunneen, Chris
Drawing on comparative work between Australia and England and Wales, this article considers issues of criminalization, racialization and youth justice. The article explores both the overt and more subtle forms of racializing and criminalizing young people and highlights the necessity for historically and situationally contextualized understandings of identity and race. The rationalities, practices and discourses of youth justice through which racialization occurs are identified, including how race itself becomes solidified as a category in which people, in many cases, from heterogeneous backgrounds, can be captured and named. In particular there is discussion of the rise of apparently neutral and non-discriminatory justifications for intervention found in the use of risk assessment that leads to racialized differentiation. It is argued that these practices both mask race in their practices and mark race in their outcomes.